Determinação de molibdênio em plantas combinando microextração e espectrometria de absorção atômica em chama - Villamizar, Jenny Andrea Oviedo (2012)
In this study, a procedure for the determination of low concentrations of molybdenum in plants by flame atomic absorption spectrometry (FAAS) was developed. The poor sensitivity of FAAS for determination of refractory elements such as molybdenum, and the typical low levels of this micronutrient in plants require the use of a preliminary preconcentration step. The procedure was based on the solidified floating organic drop microextraction strategy (SFODME). This method was selected based on its simplicity, high enrichment factors and low consumption of organic solvents. Because of SFODME microvolume characteristics, the effect of the discrete introduction of samples in FAAS was studied. The following extraction parameters were evaluated: type and concentration of complexing agent, type of solvent, solvent volume, use of ultrasound or vortex in the extraction process, and effect of discrete nebulization. All parameters were evaluated considering their effects on sensitivity for the determination of molybdenum in plant samples by FAAS. The most critical effects were caused by the type of complexing agent, the use of vortex mixing and discrete nebulization. Prior to the microextraction procedure, Mo complexing conditions were optimized. A 0.5% m v-1 8- hydroxyquinoline solution at pH 4.75 adjusted with acetate buffer and complexing time of 10 min were the ideal experimental conditions. For the microextraction procedure, the highest enhancement factor for Mo was obtained with 60 μL of 1-undecanol and using the vortex mixer for 2 min. Appreciable sensitivity improvements were observed by combining microextraction, the introduction of discrete volumes of sample, and determination of Mo by FAAS. An enrichment factor of 67, limit of detection of 4.9 μg L-1 and limit of quantification of 16.4 μg L-1 were reached. The accuracy of the developed procedure was demonstrated by determining Mo in certified reference materials. Finally, the procedure was applied to samples of roots and leaves of corn.